(untitled) (Revista Espinhaço, 2022)
The research analyzes the cotton production in Brazil in two moments. At first, we investigated the production concentrated in the southern states; in the second moment, we analyze the process that culminated in its economic displacement to the Cerrado areas, when lands were incorporated into modern agricultural production systems aimed mainly at the production of grains and feathers. The research has a descriptive and analytical character and was supported by quantitative data from international and national institutes, official institutions and the private sector. Based on the data, it was possible to establish comparisons on the global, national and regional scales on production and profitability. The results revealed that Brazil expanded cotton production and became one of the main cotton producing countries, whose average profitability exceeded the world’s. There was a spatial reconfiguration of national production and its economic displacement to the Cerrado areas. Mato Grosso and Bahia became, in isolation, the main producing states of feathers, followed by a second group, which includes Minas Gerais. In the early 2000s, the Government of Minas Gerais created incentives for the cotton production chain. Since then, there has been a constant specialization of cotton farming in Minas and the spatial reconfiguration of its production. Some municipalities in Minas Gerais showed significant growth in cotton production.